Redundant Residue Number System (RRNS) Di-Base Table for SOLiD Sequencing - Akanbasiam, Joshua Apigagua; Boateng, Kwame Osei; Addo, Matthew Glover (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2024)
The next-generation sequencing (NGS) methodology, sequencing by oligonucleotide ligation and detection (SOLiD) uses a di-base table, a somewhat unusual method, to decode sequences. Its coding scheme is based on the binary number system. The di-base table is not connected to the genetic code, nor is the coding scheme structured in the space of an entire number system. Gamow also revealed the hidden attribute of a 4 × 4 code for the di-base table, supporting his proposal of a 4 × 4 × 4 codons for the genetic code. Consideration for digital applications has focused more on the Residue Number System (RNS) and Redundant Residue Number System (RRNS) lately. Consequently, an RRNS di-base table based on the number tree concept is designed. The designed RRNS di-base table deviates from the canonical di-base table but retains every attribute necessary for effective SOLiD decoding. It shares a close relationship with the RNS-Genetic code and this presents a compelling argument for creating a single instrument that possesses the capabilities of both the genetic code and the di-base table.